TEACHING AND LEARNING ENGLISH LANGUAGE IN PUBLIC SCHOOLS: PURPOSES AND CHALLENGES - Costa, Rosemeire Parada Granada Milhomens da; Mendes, Maria Elaine (REVISTA CEREUS, 2014)
This work consists of the first part of a research conducted in the second semester of 2013 in public schools in Gurupi - Tocantins - Brazil, which aims to investigate how the process of teaching and learning English language takes place during the high school years and what their weaknesses are. It is understood to be necessary a survey that generated data in order to detect the causes of such failures and for this, the following questions emerged: ( i ) Do the methods used by schools correspond to the needs and objectives proposed? ( ii ) Is the number of classes enough for teachers to work the four skills required (reading, speaking, listening and writing)? ( iii ) Why are teachers and students so demotivated? The methodology used for this study consists of questionnaires given to 90 high school students from 3 different schools. The results showed: a) an interest from students in learning English Language b) a lack of use of the target language by teachers c) the recognition of the importance of learning a second language by students d) the writing skill as the most used by the teacher in the classroom, e) the excessive number of students per classroom. At the end of this stage we considered that the failures can be, amongst others, the result from issues within the educational system that prepares these teachers as well as inappropriate physical, curricular and didactic structures for teaching. Keywords: Teaching and learning of English, Motivation. Public schools.